Sistem Pakar Diagnosa Dampak Penggunaan Eyelash Extension Menggunakan Metode Naïve Bayes - Syaputra, Sandy; Elfianty, Lena; Alinse, Rizka Tri (LPPM UNIKA Santo Thomas Medan, 2023)
SS Beauty Bar is a beauty salon that offers many treatments, namely, nail art, eyebrow embroidery, lip embroidery, eyelash extension, facial, bb glow, lash lift, massage, SPA, menicure, pedicure, etc. One of the current treatments that are popular with women is to decorate the eyes by adding eyelashes or better known as eyelash extensions. Eyelash extension is the process of connecting artificial eyelashes with real eyelashes. An expert system for diagnosing the impact of using eyelash extensions at SS Beauty Bengkulu City was created to help diagnose the impact of using eyelash extensions based on the symptoms felt by the customer. The expert system for diagnosing the impact of using eyelash extensions at SS Beauty Bengkulu City has implemented the Naive Bayes method which is used to obtain a percentage level of the impact of using eyelash extensions and provide recommended solutions for customers. The expert system for diagnosing the impact of using eyelash extensions on SS Beauty in Bengkulu City was created using the Visual Basic.Net programming language. The expert system for diagnosing the impact of using eyelash extensions at SS Beauty Bengkulu City can provide information on the results of consultations in determining the impact of using eyelash extensions based on the symptoms that have been selected. Based on the results of the tests that have been carried out, the functionality of the expert system for diagnosing the impact of using eyelash extensions at SS Beauty Bengkulu City has gone well as expected.